The vagus nerve: An old but new player in brain–body communication - Ma, Li; Wang, Han-Bing; Hashimoto, Kenji (Brain, behavior, and immunity, 2025)
•Body–brain communication is essential for regulating immune system function.•Vagus nerve is a key mediator in body–brain communication.•The caudal nucleus of the solitary tract is the primary site influenced by vagus nerve signaling.•The gut-brain axis, mediated by the vagus nerve, is implicated in neuropsychiatricdisorders.•Transcutaneous auricular vagus nerve stimulation holds potential as a therapeutic intervention. The vagus nerve is a crucial component of the parasympathetic nervous system, facilitating communication between the brain and various organs, including the ears, heart, lungs, pancreas, spleen, and gastrointestinal tract. The caudal nucleus of the solitary tract in the brainstem is the initial site regulated by the vagus nerve in brain–body communication, including the interactions with immune system. Increasing evidence suggests that the gut–brain axis, via the vagus nerve, may play a role in the development and progression of psychiatric, neurologic, and inflammation-related disorders. Population-based cohort studies indicate that truncal vagotomy may reduce the risk of neurological disorders such as Parkinson’s disease and Alzheimer’s disease, underscoring the vagus nerve’s significance in these conditions. Given its role in the cholinergic anti-inflammatory pathway, α7 nicotinic acetylcholine receptors present a potential therapeutic target. Additionally, noninvasive transcutaneous auricular vagus nerve stimulation (taVNS) shows promise as a therapeutic tool for these disorders. This article provides a historical review of the vagus nerve and explores its role in brain–body communication. Finally, we discuss future directions, including the potential of noninvasive taVNS as a therapeutic approach.